Thepade’s Sorted Ternary Block Truncation Coding with Score level fusion for Multimodal Biometric Identification using Iris &Palmprint - Rupali K, Bhondave; Thepade, Sudeep (International Journal of Computer Sciences and Engineering, 2015)
The fusion of multiple biometric traits helps to increase accuracy in terms of genuine acceptance ratio (GAR). Here Iris and Palmprint fusion at Matching Score level is performed. The feature extraction in spatial domain using Thepade’s sorted ternary block truncation coding is taken here to reduce the feature vector size of image. Iris and Palmprint are together taken here for identification. The test beds of 60 pairs of Iris and Palmprint samples of 10 persons (6 per person of iris as well as Palmprint) are used as test bed for experimentation. Experimental result in matching score proportion of Iris: Palmprint (1:4) using TSTBTC given better performance as indicated by higher GAR values than all other scores for matching score level fusion of proposed multimodal biometric identification using TSTBTC.